TINJAUAN YURIDIS ATAS UPAYA REFORMASI DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA DALAM MENCIPTAKAN TATANAN NEGARA-NEGARA DI DUNIA YANG BERDAULAT, DAMAI, DAN ADIL - Ahmad Junaidi P; Arif Arif; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2014)
ABSTRACT The UN Security Council is one of United Nations organization that has important role among the other organizations because there is a special right given to the five members of the UN Security Council called a ‘veto’. But over time and based on the age development with the complexity of global issue, there are many countries who have opinion that the UN Security Council is not suitable to the present global situation and condition. For a number of years now, there have been calls for the Security Council to be modified, modernized, and reformed. To date there exist multiple proposals on how to reform the Security Council and have been submitted to the UN General Assembly for approval. But the reform of the United Nations Security Council has not yet success because there are obstacles that disturb the reform process of the UN Security Council. This article would like to discuss about the reform of the United Nations Security Council and what the reason of the reform, and what the obstacles to the reform of the United Nations Security Council and what the law provision on reforming the United Nations Security Council. In order to support the discussion and analysis of the aforementioned issue, this research applies normative law approach and descriptive study as research method. The data is collected from library research and analyzed by qualitative study. Keyword: Reform, Security Council, Veto, United Nations.